Het Hodshonhuis in Haarlem, onderzoek aan de achttiende-eeuwse Blauwe Zaal (Bulletin KNOB, 2000)
During the colour research of the Blue Room in the late eighteenth century Hodshon house in Haarlem it appeared that the colour combination found in 1996 does not match the original colour scheme. Through stratigraphical and sample research the original appearance in 1796 was mapped. Besides Prussian blue, used for the dark-blue stucco fields and overdoors, an unusual pigment was analysed for the light-blue colour on the other walls: ‘blue verditer’.The possibilities of conserving the interior were examined, as well as the options for making the colour scheme visible again either by clearing or by reconstruction. Clearing proved to be impossible because of the painting systems applied in the past. A reconstruction is technically possible when an intermediate layer of lime in an acrylic dispersion is first applied on the present package of repaintings. The colouring layer of lime with the pigment blue verditer can be applied on this intermediate layer. Thus not only the original layer package of the Blue Room is preserved, but the architectonic articulation is also reinforced by the renovated colour combination.The research was executed within the framework of the restoration course specializing in historical interior spaces. It forms part of the completion of the education at Stichting Restauratie Atelier Limburg in Maastricht and ICN Education division in Amsterdam.